2016
DOI: 10.14419/ijaes.v4i1.5721
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between real and accrual-based earnings management: analysis based on the mandatory IFRS adoption

Abstract: The main purpose of this paper is to examine the relation between real and accrual-based earnings management after the mandatory IFRS adoption. I focus on a sample of 124 firms drawn from the 250 French-listed companies during the period from 1999 to 2011. Empirical results indicate that French firms use real activities manipulation and discretionary accruals as complementary tools to smooth earnings. Finally, unlike previous studies, I don't find evidence of the sequential nature between the two earnings mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Das, Mishra, and Rajib (2017) studied Indian firms by measuring AEM and REM as modified by Jones (1991) and Roychowdhury (2006), respectively. The result presented the complementary relationship between AEM and REM that was consistent with the finding of Sellami (2016) who also found evidence that, after mandatory international financial reporting standards (IFRS) adoption in French, managers use REM and AEM simultaneously. There is supporting evidence from Taiwan, Indonesia, and Japanese, where researchers documented firms using AEM and REM simultaneously to meet earnings target (Chen, Huang, & Fan, 2012;Matsuura, 2008;Sanjaya & Saragih, 2012).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Das, Mishra, and Rajib (2017) studied Indian firms by measuring AEM and REM as modified by Jones (1991) and Roychowdhury (2006), respectively. The result presented the complementary relationship between AEM and REM that was consistent with the finding of Sellami (2016) who also found evidence that, after mandatory international financial reporting standards (IFRS) adoption in French, managers use REM and AEM simultaneously. There is supporting evidence from Taiwan, Indonesia, and Japanese, where researchers documented firms using AEM and REM simultaneously to meet earnings target (Chen, Huang, & Fan, 2012;Matsuura, 2008;Sanjaya & Saragih, 2012).…”
Section: Introductionsupporting
confidence: 88%
“…Their results found a complementary relationship between AEM and REM. The findings of Sellami (2016) also demonstrate evidence of the mandatory IFRS adoption of use REM and AEM simultaneously by French managers.…”
Section: The Association Between Aem and Remmentioning
confidence: 54%
“…This research examines the interaction between accrual-based earnings management and real earnings management practices as a strategy for meeting earnings targets. Prior studies have shown evidence that firms make choices between accruals and real earnings management (Alhadab & Nguyen, 2018;Baker et al, 2019;Cohen et al, 2008;Cohen & Zarowin, 2010;Sellami, 2016;Zang, 2012) , however, with the exception of Zang (2012), studies depicting the sequential nature of both earning management practices remain scarce so that further investigation of the sequential nature of both earnings managements is necessary. This research provides evidence that managers use a combination of accruals and real earnings management to meet earnings targets and shows that real and accruals earnings management have a sequential nature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study of Sellami (2016) analyzed the AEM and REM of French registered firms, over a time period of 1999 to 2011. The findings of the study confirmed that companies manage income and use REM to smoothen out their incomes.…”
Section: Literature Reviewmentioning
confidence: 99%